Waves of simulation: Arguing authenticity in an era of surfing the hyperreal. (March 2020) - Roberts, Michael; Ponting, Jess
This article is an examination of the impact of new, technologically sophisticated wave pools upon the culture of surfers. Appropriating the concepts of simulation from the work of postmodern theorist Jean Baudrillard, and mechanical reproduction from the critical theorist Walter Benjamin, we consider how the spectre of perfectly simulated waves in controlled environments has signaled a new era in the history of the social construction and contestation of authenticity within the surfing world. Through an examination of interview and survey data that reveals contrasting perspectives on wave pools, we consider the implications of the possibility that with the invention of the perfectly simulated wave, the experience of riding a wave will be detached from the domain of tradition that is known as the surfing lifestyle. Our article compliments previously published research on lifestyle sports that take place in artificial settings.